Answer: 11x-36
Step-by-step explanation:
Answer:
Step-by-step explanation:
Answer:
![\large\boxed{(-2z^2-14)-(-12z^2)=10z^2-14}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B%28-2z%5E2-14%29-%28-12z%5E2%29%3D10z%5E2-14%7D)
Step-by-step explanation:
![(-2z^2-14)-(-12z^2)=-2z^2-14+12z^2\qquad\text{combine like terms}\\\\=(-2z^2+12z^2)-14=10z^2-14](https://tex.z-dn.net/?f=%28-2z%5E2-14%29-%28-12z%5E2%29%3D-2z%5E2-14%2B12z%5E2%5Cqquad%5Ctext%7Bcombine%20like%20terms%7D%5C%5C%5C%5C%3D%28-2z%5E2%2B12z%5E2%29-14%3D10z%5E2-14)
Answer:
-1.5
Step-by-step explanation:
4x² + 4x - 3 = 0
(2x + 3)(2x - 1) = 0
2x + 3 = 0 or 2x - 1 = 0
x = -3/2 or x = 1/2
Answer: -1.5
Answer:
A loss of weight means we subtract from Jack's current weight.
Step-by-step explanation:
A loss of weight means we subtract from Jack's current weight. New Weight = Current Weight - Weight Loss per week * number of weeksNew Weight =257 - 3*12New Weight =257 - 36New Weight = 221